2021
DOI: 10.4025/actasciagron.v43i1.50519
|View full text |Cite
|
Sign up to set email alerts
|

The use of hydrogen cyanamide or nitrogen fertilizer increases vegetative and productive performance of fig cv. Roxo de Valinhos

Abstract: Some plants do not demand a lot of chilling hours, but methods to overcome dormancy promote more vigorous and productive plant. This study aimed to assess hydrogen cyanamide and nitrogen fertilizer with different concentration to growth and production in ‘Roxo de Valinhos’ fig tree. Two crop cycles (2015/2016 and 2016/2017) was performed in São Manuel city, São Paulo State, Brazil. Phenological and productive data was evaluated in a 2 x 5 factorial (Product x Concentration), organized in randomized complete bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…When the accumulated cold hours are insufficient to break dormancy, it is common to use sprouting inducers, such as hydrogen cyanamide (Dormex ® ) and Erger ® , a product that presents organic nitrogen in its composition and presented a good performance anticipating the sprouting and promoted a higher number of buds overcome the dormancy in fig 'Roxo de Valinhos' (Souza et al, 2021). During the process of induction and overcoming of dormancy, several changes occur in the chemical components of plant tissues, mainly in the buds (Seif Elyazal & Rady, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…When the accumulated cold hours are insufficient to break dormancy, it is common to use sprouting inducers, such as hydrogen cyanamide (Dormex ® ) and Erger ® , a product that presents organic nitrogen in its composition and presented a good performance anticipating the sprouting and promoted a higher number of buds overcome the dormancy in fig 'Roxo de Valinhos' (Souza et al, 2021). During the process of induction and overcoming of dormancy, several changes occur in the chemical components of plant tissues, mainly in the buds (Seif Elyazal & Rady, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the reduction in FSR observed after a specific accumulation of chilling was related to the lack of sufficiently high temperatures for sprouting. Figs respond to higher temperatures at the end of winter with an increase in respiratory activity due to the reduction of inhibitors and increase in growth promoters (Souza et al, 2021). Ferraz et al (2020) assessed the phenology of fig cultivars and concluded that Roxo de Valinhos reached the budding stage more quickly than Troyano, which is classified as having a longer harvest cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Vossen and Silver (2000) reported that this species requires 0-150 chilling hours to overcome dormancy depending on cultivar. Chilling accumulation varies by genotype because each cultivar has distinct thermal requirements (Souza et al, 2021). Although the fig tree is grown in regions with mild winters, the development of buds can be unpredictable, which hinders production (Flaishman, Rover, & Stover, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The HC has stood out due to its expressive outcomes allowing better performance to overcome dormancy (Souza et al, 2021) and HC 0.6% is widely used by peaches growers in subtropical regions of São Paulo state, Brazil (Ferreira et al, 2019). However, despite these most evident results, this chemical has been shown a rather toxicity to the repeated exposure by applicators (Hernández and Craig, 2016).…”
Section: Introductionmentioning
confidence: 99%